A Strategic Approach for African Agricultural Universities Experiencing Low Human Capacity to Engage in Graduate-Level Training: Lessons from Gulu University in Uganda - Ongeng, D. (My University, 2016)
The significance of agriculture in driving Africa’s growth and development has greatly gained recognition in the recent past. African universities are expected to play a critical role in African agricultural development process because of their inherent pivotal role in human capital development and agro-technology generation. Many universities in Africa are plagued with low human capacity, a key factor, which has continued to undermine their contribution to economic development in the continent. The most glaring capacity gap is evident at graduate-level training. Therefore, this paper shares lessons based on experience from Gulu University in Uganda on how agricultural universities experiencing human resource capacity gaps can innovatively venture into high quality PhD-level training. The paper describes innovation in curriculum process that led to the development and mounting of a thematic area-based taught PhD program in the Faculty of Agriculture and Environment. This PhD model is considered as an “accommodative strategy” suitable for human resource-constrained universities as it allows for effective use of existing limited human capacity while providing room for expansion within the same curriculum structure concomitant with staff capacity improvement.
Keywords: African universities, graduate-level training, Gulu University, human capacity constraint, thematic area-based PhD model